2007
DOI: 10.1016/j.jcrs.2007.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Validity of autorefraction after cataract surgery with multifocal ReZoom intraocular lens implantation

Abstract: Although autorefraction showed excellent agreement with subjective refractive astigmatism, correlation with spherical values was poor, with a trend toward more negative values. Autorefraction after ReZoom IOL implantation can be used as a good starting point for subjective refraction of astigmatism; however, spherical values should be underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 32 publications
4
42
2
2
Order By: Relevance
“…Consequently, the accuracy and precision of the autorefractor measurements in MCL over-refraction is comparable to MIOL over-refraction. On the other hand, Muñoz et al [16] found mean differences of −1.00 ± 0.61D and statistically significant differences when measuring a refractive MIOL, a result that differs from the measurements performed in this preliminary study and from Bissen-Miyajima's data. Muñoz et al argued that these differences were caused by the geometry of the IOL they used (refractive multifocal ReZoom ® , Abbott Medical Optics, Inc.), which can interfere with the infrared beam of the autorefractor.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Consequently, the accuracy and precision of the autorefractor measurements in MCL over-refraction is comparable to MIOL over-refraction. On the other hand, Muñoz et al [16] found mean differences of −1.00 ± 0.61D and statistically significant differences when measuring a refractive MIOL, a result that differs from the measurements performed in this preliminary study and from Bissen-Miyajima's data. Muñoz et al argued that these differences were caused by the geometry of the IOL they used (refractive multifocal ReZoom ® , Abbott Medical Optics, Inc.), which can interfere with the infrared beam of the autorefractor.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, in astigmatic vectors the differences found were not statistically significant for all MCL considered together and when the different MCL were analyzed. The results with MCL are in good agreement with the results obtained by other authors [15,16] that used autorefraction in patients with MIOL and who found mean differences close to zero and good Pearson's correlation coefficients. Moreover, when comparing the performance of the autorefractor with and without MCL, the results can be considered similar.…”
Section: Refraction Datasupporting
confidence: 90%
See 1 more Smart Citation
“…9 Refractive IOLs provide multifocality by changing the IOL refraction based on pupil size. Autorefraction is measured with infrared light reflected through small apertures.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of eyes with a refractive multifocal IOL using autorefraction show low accuracy. 9 The usefulness of autorefraction as a starting point for autorefraction in eyes with a diffractive multifocal IOL has been reported. 10 However, the reliability of autorefractometry for diffractive multifocal IOLs has not been precisely reported.…”
mentioning
confidence: 99%